DAMPAK ALIH GUNA HUTAN MENJADI LAHAN PERTANIAN TERHADAP KEANEKARAGAMAN KUMBANG TINJA (COLEOPTERA: SCARABAEIDAE) DI SEKITAR TAMAN NASIONAL LORE LINDU - Shahabuddin, Shahabuddin (AgriSains, 2005)
A study was conducted to evaluated effect of forest convertion to agriculture land on diversity of dung beetles which play a major role in decomposition of animal dung and carcasses. Sample was collected from Lore Lindu national Park at different land use type i.e. primary forest, secondary forest, cacao plantation ad maize field. I recorded 18 species of dung beetles from all study sites. The result showed that there were a reduction of dung beetles diversity due to forest convertion. The species number of dung beetles at primary forest was two times higher than those in secondary forest and was three times higher compared to those in cacao plantation and maize field. Furthermore, species composition of dung beetles at primary forest was significantly different compared to all other land use type.Key words : Forest conversion, diversity, dung beetles, conservation